Value of ultrasound in evaluation of cervical lymphadenopathy: correlation with FNAC / histopathology - Jaiswal, Pooja; Sharma, Prakash (Journal of Society of Surgeons of Nepal, 2016)
Introduction: The role of high-resolution ultrasound in evaluation of cervical lymph nodes is well established. The aim of this study was to determine its accuracy in differentiating benign and malignant cervical lymphadenopathy. The objectives were to study various sonographic features applicable in routine clinical practice to identify and differentiate various types of cervical lymphadenopathy. Methods: The study was done at the Pathology and Radiology department of Manipal teaching hospital (MTH) from Jan 2015 to Dec 2015. Seventy cervical nodes in 70 patients (17-reactive, 23-tuberculous, 9-lymphoma and 21-metastatic) were evaluated by high resolution ultrasound (7.5- 10MHz). Shape (S:L ratio), (maximal short to maximal long axis ratio diameter) nodal margins, hilar echogenicity, vascular pattern, distribution, size, echogenicity, calcification, posterior enhancement, eccentric cortical hypertrophy, matting and soft tissue edema were assessed. Confirmed diagnosis was either made by USG guided FNAC on the largest node or by open biopsy. The first four parameters had the most significant differences between benign and malignant lymph nodes and were evaluated to calculate the accuracy of ultrasound in their differentiation. Individual groups were compared and optimal sonographic features in differential diagnosis were determined. Results: The common useful sonographic features to identify different types of cervical lymph nodes were S:L ratio, nodal margins, hilar echogenicity, vascular pattern, matting, soft tissue edema, echogeneity, intranodal necrosis, displaced hilar vascularity, eccentric cortical hypertrophy and posterior enhancement. Vascularity was the most accurate parameter (86%) when used in isolation and when combined parameters were used ultrasound had accuracy of 97% in diagnosing benign or malignant cervical lymphadenopathy. Conclusion: This study showed that high resolution ultrasound has a high degree of accuracy in differentiating benign and malignant cervical lymphadenopathy and assists in differentiating various causes of lymphadenopathy.